2021
DOI: 10.1016/j.ijans.2021.100328
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for clinical practice amidst coronavirus among nursing students in southwest Nigeria

Abstract: Background COVID-19 is a public health problem that has claimed the lives of many men, women, and children globally, apart from its overwhelming economic impact. Nurses are inexorably faced with this situation as part of the frontline hospital workers, likewise student nurses on clinical practice while on training. Objective To assess readiness on resumption for clinical practice amidst coronavirus pandemic among Nursing students in South-West Nigeria Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Results of the present study indicate a high level of intention to attend limited face‐to‐face classes. Similarly, nursing students in Nigeria reported to be highly ready for clinical practice amid the pandemic 26 . After almost 2 years of their curriculum being delivered via online and remote learning due to the pandemic, it is understandable that students desire in‐person classes as they faced a number of challenges and stressors in online learning 5,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the present study indicate a high level of intention to attend limited face‐to‐face classes. Similarly, nursing students in Nigeria reported to be highly ready for clinical practice amid the pandemic 26 . After almost 2 years of their curriculum being delivered via online and remote learning due to the pandemic, it is understandable that students desire in‐person classes as they faced a number of challenges and stressors in online learning 5,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, nursing students in Nigeria reported to be highly ready for clinical practice amid the pandemic. 26 After almost 2 years of their curriculum being delivered via online and remote learning due to the pandemic, it is understandable that students desire in-person classes as they faced a number of challenges and stressors in online learning. 5,27 Moreover, around 2000 h of laboratory and clinical exposure are required in the current undergraduate nursing curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested the importance of enhancing the clinical competence of nursing students to work in areas of infectious diseases like coronavirus. 25…”
Section: Discussionmentioning
confidence: 99%